Making sense of social problem - "Best, Joel (ed.); Harris, Scott R. (ed.)" (New Delhi, 2017)
Internet addiction. Cell-phone-distracted drivers. Teen suicide. Economic recession. The health risks of trans fats. The carefully selected collection of case studies in Making Sense of Social Problems is designed to help students understand and critically evaluate a wide range of contemporary social issues. The cases are organised to highlight a series of key elements: why "objective" claims deserve critical attention how advocates bring attention to issues why expert interpretations may change over time the role of the media in shaping or distorting concerns the consequences of public policy The introduction, conclusion, and section notes provide a coherent framework for the text. Reflecting the promise of the constructionist approach, the result is a powerful set of tools for systematically investigating social problems. It can be used to advantage as a "stand-alone," as well as with such texts as Joel Best's Social Problems.
Keywords: Social problems